Universal human rights in theory and practice - Donnelly, Jack; Wang, Puqu (Ithaca Cornell University Press, 2003)
In this revised and updated edition, Donnelly directly engages matters of immediate political significance. He addresses recent international events and considers the theoretical issues and practical dilemmas involved in protecting human rights internationally.
Keywords: Civil rights. Human rights. Cultural relativism